2016
DOI: 10.1016/j.jsxm.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Atherosclerosis in Patients with Erectile Dysfunction: A Population-Based Study

Abstract: Introduction The presence of erectile dysfunction (ED) could be a warning of vascular disease in different arterial territories. Aim The aim of this study was to investigate the association between ED and the presence of atherosclerosis in 2 different vascular beds: carotid and lower limbs. Methods A total of 614 volunteers between 45 and 74 years of age (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The association between HTN, dyslipidaemia and ED remains controversial. Lahoz et al [57] found no significant association between ED and HTN, elevated cholesterol or triglycerides. Equally, de Boer et al [22] found the risk of HTN in ED patients to be 0.83 (95% CI 0.56-1.25).…”
Section: Association Between Ed and Cvdmentioning
confidence: 95%
See 2 more Smart Citations
“…The association between HTN, dyslipidaemia and ED remains controversial. Lahoz et al [57] found no significant association between ED and HTN, elevated cholesterol or triglycerides. Equally, de Boer et al [22] found the risk of HTN in ED patients to be 0.83 (95% CI 0.56-1.25).…”
Section: Association Between Ed and Cvdmentioning
confidence: 95%
“…When compared to men without ED, men with ED were at increased risk of ischaemic heart disease (1.08-1.87) [ [22,26,35,47,51,54] (Appendix S1 [5,16,22,26,29,35,47,51,[53][54][55][56][57][58][59]). The risk of CVD was positively associated with severity of ED [35,53,55] and increasing age [26].…”
Section: Ed and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…ED was shown to be an independent predictor of peripheral artery disease (PAD) defi ned as an ABI < 0.9 [22]. On the other hand, an ABI of < 0.9 is of limited predictive value to diagnose ED in the general population [23]. Only in diabetic and cardiovascular highrisk patients (Framingham Risk Score), an ABI of < 0.9 may be associated with and be predictive for ED [23].…”
Section: Clinical Examinationmentioning
confidence: 99%
“…On the other hand, an ABI of < 0.9 is of limited predictive value to diagnose ED in the general population [23]. Only in diabetic and cardiovascular highrisk patients (Framingham Risk Score), an ABI of < 0.9 may be associated with and be predictive for ED [23]. In line, cardiovascular risk stratifi cation in patients with suspected ED using the Framingham Risk Score is promoted by some in order to determine the diagnostic work-up [24].…”
Section: Clinical Examinationmentioning
confidence: 99%